Impaired Abcb1a function and red meat in a translational colitis mouse model induces inflammation and alters microbiota composition - Stensballe, Allan; Bennike, Tue Bjerg; Ravn-Haren, Gitte; Mortensen, Alicja; Aboo, Christopher; Knudsen, Lina Almind; Rühlemann, Malte C.; Birkelund, Svend; Bang, Corinne; Franke, Andre; Vogel, Ulla; Hansen, Axel Kornerup; et al. (Frontiers in Medicine, 2023)
Inflammatory Bowel Disease (IBD) affects approximately 0.3% of the global population, with incidence rates rising dramatically worldwide. Emerging evidence points to an interplay between exposome factors such as diet and gut microbiota, host genetics, and the immune system as crucial elements in IBD development. ATP-binding cassette (ABC) transporters, including human p-glycoprotein encoded by the ABCB1 gene, influence intestinal inflammation, and their expression may interact with environmental factors such as diet and gut microbes. Our study aimed to examine the impact of protein sources on a genetic colitis mouse model. Methods Abcb1a-deficient colitis mice were fed either casein or red meat-supplemented diets to investigate potential colitis-aggravating components in red meat and their effects on host-microbiota interactions. We conducted deep mass spectrometry-based proteomic inflammation profiling of gastrointestinal tissue (colon, ileum) and urine, and determined the overall microbiome in feces using 16S rRNA gene sequencing. Colon and systemic gut inflammation were validated through histology and immune assays, respectively. Results Proteomic analysis of intestinal tissue and urine revealed associations between ileum and urine proteomes in relation to Abcb1a deficiency. The absence of Abcb1a efflux pump function and diet-induced intestinal inflammation impacted multiple systemic immune processes, including extensive neutrophil extracellular trap (NET) components observed in relation to neutrophil degranulation throughout the gastrointestinal tract. The colitis model's microbiome differed significantly from that of wild-type mice, indicating the substantial influence of efflux transporter deficiency on microbiota. Conclusion The proteomic and microbiota analyses of a well-established murine model enabled the correlation of gastrointestinal interactions not readily identifiable in human cohorts. Insights into dysregulated biological pathways in this disease model might offer translational biomarkers based on NETs and improved understanding of IBD pathogenesis in human patients. Our findings demonstrate that drug transporter deficiency induces substantial changes in the microbiota, leading to increased levels of IBD-associated strains and resulting in intestinal inflammation.